Economic evaluation of an early childhood development center–based agriculture and nutrition intervention in Malawi - Gelli, Aulo; Kemp, C. G.; Margolies, Amy; Twalibu, Aisha; Katundu, Mangani; Levin, Carol E. (Springer, 2022)
Malnutrition is a leading cause of death and disability among children in low-income countries. Nutrition-sensitive interventions show promise in increasing food access and improving diets. There are possible synergies of integrating these programs with other sectors, improving effectiveness by leveraging resources. However, economic evaluations of these multi-sectoral programs are limited. We aimed to estimate the cost efficiency, cost-effectiveness, benefit-cost ratio, and net benefit of using community-based early childhood development (ECD) centers as platforms for an intervention promoting agricultural production and nutrition among households with young children in Malawi. The intervention was costed using bottom-up micro-costing and top-down expenditure analysis with a societal perspective and a 12-month horizon. Effectiveness estimates were derived from a cluster-randomized control trial. Premature deaths and stunting cases averted were estimated using the Lived Saved Tool. We calculated DALYs averted, and the value of three benefits streams resulting from reductions in premature mortality, increases in lifetime productivity and household agricultural productivity. We transferred the US value of a statistical life (VSL) to Malawi using an income elasticity of 1.5, and a 10% discount rate. Probabilistic sensitivity analysis was conducted using a Monte Carlo model. The intervention cost $197,377, reaching 4,806 beneficiaries at $41 per beneficiary, $595 per case of stunting, $18,310 per death, and $516 per DALY averted. Net benefit estimates ranged from $507,589 to $4,678,258, and benefit-cost ratios from 3.57 to 24.70. Sensitivity analyses confirmed a positive return on investment. Implementing agriculture-nutrition interventions through ECD platforms may be an efficient use of resources in Malawi and similar contexts.